The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/rs11070745
|View full text |Cite
|
Sign up to set email alerts
|

Mining Deformation Life Cycle in the Light of InSAR and Deformation Models

Abstract: The Sentinel-1 constellation provides an effective new radar instrument with a short revisit time of six days for the monitoring of intensive mining surface deformations. Our goal is to investigate in detail and to bring new comprehension of the mine life cycle. The dynamics of mining, especially in the case of horizontally evolving longwall technology, exhibit rapid surface changes. We use the classical approach of differential radar interferometry (DInSAR) with short temporal baselines (six days), which resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…In contrast, consecutive DInSAR was able to capture fast deformation that reached −1.0 m in the vertical direction. Similar results were obtained in [4,7], in which the convergence of DInSAR results and mining modeling for USCB mines was studied. The deformation time series generated for selected points in large deformation spots demonstrate a reasonable agreement with the Knothe mining deformation model (e.g., see [4]) for spots (a) and (c) (Figure 9).…”
Section: Comparison Between Sbas and Dinsar Deformation Estimation Ansupporting
confidence: 78%
See 3 more Smart Citations
“…In contrast, consecutive DInSAR was able to capture fast deformation that reached −1.0 m in the vertical direction. Similar results were obtained in [4,7], in which the convergence of DInSAR results and mining modeling for USCB mines was studied. The deformation time series generated for selected points in large deformation spots demonstrate a reasonable agreement with the Knothe mining deformation model (e.g., see [4]) for spots (a) and (c) (Figure 9).…”
Section: Comparison Between Sbas and Dinsar Deformation Estimation Ansupporting
confidence: 78%
“…Thus, we do not describe interferometric principles in this work. Many studies have demonstrated the effective application of DInSAR for monitoring fast terrain displacements [4][5][6][7][8]. DInSAR provides reliable results when the displacement rate is much higher than atmospheric artifacts [35].…”
Section: Multi-temporal Consecutive Dinsar Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Upper Silesian Coal Basin (USCB) which is located in Southern Poland covers an area of almost 6000km 2 (Przyłucka et al, 2016). Coal exploitation in the USCB dated back the nineteenth century (Ilieva et al, 2019). Coal exploitation performed underground has its consequence in ground movements such as subsidence, sinking or shaking (Mutke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%